KEARIFAN LOKAL BUKA RANTAU LARANGAN DI DESA ROKAN KOTO RUANG KECAMATAN ROKAN IV KOTO KABUPATEN ROKAN HULU - Sihotang, Mona Oktavia; Susanti, Rina (Jurnal Sains Riset, 2024)
Buka rantau larangan is a local wisdom as a community effort based on customary agreements to preserve the river ecosystem in Rokan Koto Ruang Village. This study aims to describe the stages of implementing buka rantau larangan and identify the values contained in buka rantau larangan with a social system theory approach by Walter Buckley. The technique of determining informants is the Quota sampling technique. The subjects in the study consisted of 7 people who had a role as managers of buka ratau larangan. Primary and secondary data collection using observation techniques, in-depth interviews and documentation. The results showed that there are several stages in the implementation of open rantau larangan, namely: 1) Preparation for opening rantau larangan, 2) Implementation of the opening of the rantau larangan and 3) After the implementation of the opening of the rantau larangan. The implementation of open rantau larangan cannot be separated from the values contained in it. These values are the value of togetherness, the value of mutual cooperation, the value of compatibility, the value of love for nature, the value of obedience and the value of kinship.